145 PELAKSANAAN PERLINDUNGAN HUKUM ATAS UPAH BAGI PEKERJA MIGRAN DI DAERAH ISTIMEWA YOGYAKARTA - Wiwin Budi Pratiwi (Universitas Muhammadiyah Gresik, 2018)
Cases of Indonesian migrant workers who are not paid their pay or get pay that are not in accordance with the employment agreement still occur. BP3TKI Yogyakarta receives a complaint report from migrant workers who have returned to Indonesia related to unpaid wages. Therefore, a solution is needed to be able to give the right to wages for migrant workers. The purpose of this study was to analyze the implementation of legal protection for wages for Indonesian migrant workers in the Yogyakarta Special Region.The type of research used in this study is empirical juridical. The location of this research is in Yogyakarta Special Region. Data collection techniques in the form of interviews and document studies. Data analysis was carried out in a qualitative descriptive manner.The results of the study show that the fulfillment of the right to wages after migrant workers return to Indonesia has a problem in the settlement because the position of migrant workers has returned to Indonesia. Many cases occur only because Indonesian migrant workers, especially those from Yogyakarta Special Region, do not report to the BP3TKI Yogyakarta with the reason that they are reluctant to take care of and do not have confidence that their rights will be fulfilled. Cases of settlement of existing wages have been successfully resolved through mediation efforts between BP3TKI Yogyakarta and migrant workers / families of migrant workers and agents that channel migrant workers to work abroad. In addition to efforts through mediation, a method was also taken, namely with the BP3TKI Yogyakarta sending a letter of request for settlement assistance to the Indonesian Embassy. The Indonesian Embassy will mediate with the employer / company where the migrant worker works to fulfill the rights of the migrant worker who has returned to Indonesia.